Explaining the collapse of the prison population in the Netherlands: Testing the theories - Boone, Miranda (European journal of criminology, 2022)
Between 2005 and 2015 the Dutch prison population decreased by 44 percent. Such a rapid yet sustained reduction in the number of prisoners has no parallel in the Western world in this period. What are the factors that underlie this unique development? This article charts the decline of prisoner numbers in the Netherlands and considers areas that may account for it. It takes a systemic approach which considers publicly available data that has involved the whole of the criminal justice system. It finds that a serious decline in crimes reported to the police is part of the explanation. Although the overall percentage of cases solved by the police has not changed and the prosecution office has not become more reluctant to forward cases to court, fewer cases that warrant imprisonment have come before the court over this period. In addition, the average sentence length imposed by judges has gone down. The proportion of acquittals has gone up. This shows that any explanation should involve developments in policing as well as in the courtroom. However, questions regarding police capacity to deal with serious and organized crime call into question any conclusion that the Dutch carceral collapse is simply due to a decrease in crime. The reality underlying this remarkable reduction in the number of people in prison at any one time in the Netherlands requires a more multifaceted answer than this.